2020
DOI: 10.1088/1742-6596/1578/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationship between Physical Exercise, Psychological Flexibility and Positive Emotion of College Students Based on Computer Mathematical Model

Abstract: In the 1970s and 1980s, the study of mental resilience emerged in the field of psychology in the United States and quickly became a hot topic in the field of international psychology. The field studies the psychological adaptation and development of children, adolescents (and later adults) in adversity. The extensive research on the psychological resilience of college students can enlighten the complexity of their psychological development. Throughout life, people inevitably encounter setbacks and adversities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Consistent with the previous studies [ 13 , 14 , 15 , 16 ], we found that physical activity was positively associated with resilience in our college student sample. The result is also supported by Hjemdal et al, who have argued that physical activity serves an important function in promoting psychological resilience [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with the previous studies [ 13 , 14 , 15 , 16 ], we found that physical activity was positively associated with resilience in our college student sample. The result is also supported by Hjemdal et al, who have argued that physical activity serves an important function in promoting psychological resilience [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Evidence exists that physical activity is positively and significantly associated with resilience [ 13 ]. Secer and Yildizhan have suggested that the level of physical activity is an important variable that influences the psychological resilience level of university students [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of positive emotion, physical exercise can also promote the production of individual positive emotion. When individuals experience more positive emotion, the proportion of negative emotions is significantly reduced, which helps individuals form positive and optimistic attitudes, have a greater sense of hope, and show higher life satisfaction ( Ligeza et al, 2019 ; Bo et al, 2020 ). The results also showed that the mediation path of positive emotion has the greatest influence on the total mediation effect, indicating that the influence of physical exercise on life satisfaction is largely played by positive emotion.…”
Section: Discussionmentioning
confidence: 99%